Living Constitution in Islamic Constitutional Law: A Comparative Study of Gorontalo Customary Constitutional Law in Majority and Minority Enclave Contexts - Moonti, Roy Marthen; Akili, Rustam Hs.; Kadir, Yusrianto; Bunga, Marten; Halfaoui, Amro (IAIN Manado, 2025)
This study analyzes the operationalization of Gorontalo customary law as a living constitution within the framework of Islamic Constitutional Law in two different demographic contexts: a Muslim majority society in Gorontalo Province (98.1%) and a Muslim minority enclave in Ternate Tanjung Sub-District, Manado City (86.7% at the sub-district level and 31.9% at the city level). Using a socio-legal comparative research approach, this study examines how adat-Islamic constitutional norms function, adapt, and obtain legitimacy within different constitutional structures. Data were collected through in-depth interviews with four key informants, comprising two Gorontalo customary leaders and two Manado community leaders. The findings demonstrate that the principle